Optogenetic probing of functional brain circuitry - Mancuso, James J.; Kim, Jinsook; Lee, Soojung; Tsuda, Sachiko; Chow, Nicholas B. H.; Augustine, George J. (WILEY, 2011)
Recently developed optogenetic technologies offer the promise of high-speed mapping of brain circuitry. Genetically targeted light-gated channels and pumps, such as channelrhodopsins and halorhodopsin, allow optical control of neuronal activity with high spatial and temporal resolution. Optogenetic probes of neuronal activity, such as Clomeleon and Mermaid, allow light to be used to monitor the activity of a genetically defined population of neurons. Combining these two complementary sets of optogenetic probes will make it possible to perform all-optical circuit mapping. Owing to the improved efficiency and higher speed of data acquisition, this hybrid approach should enable high-throughput mapping of brain circuitry.
Keywords: IMAGING SYNAPTIC INHIBITION; GREEN FLUORESCENT PROTEINS; NEURAL CIRCUITRY; TRANSGENIC MICE; CHLORIDE INDICATOR; OPTICAL CONTROL; SENSITIVE DYES; IN-VIVO; CHANNEL; VOLTAGE